Mediating Métis Identity: An Interview with Jennifer Adese and Zoe Todd - Jennifer Adese; Zoe Todd; Shaun Stevenson (MediaTropes, 2017)
In this interview, Métis scholars and writers, Jennifer Adese and Zoe Todd, engage in conversation with settler scholar and PhD candidate, Shaun Stevenson, about the complex mediations of Métis identity. Pushing back against limited notions of “mixedness” and uncritical settler or non-Métis moves to indigenize at the expense of Métis peoplehood and self-determination, the authors articulate a robust mediation of Métis identity, which occurs through kinship relations, connections to a Métis homeland and polity, the potential for language revitalization, and the foregrounding of Métis women. The authors assert that Métis identity has been overdetermined through uncritical mediations of settler identity, as they shift the terms of conversation back to Métis peoples themselves, in order to articulate a distinct vision of Métis futurity.